2007
DOI: 10.1111/j.1467-9280.2007.01858.x
|View full text |Cite
|
Sign up to set email alerts
|

Animals and Androids

Abstract: People commonly ascribe lesser humanness to others than to themselves. Two senses of humanness appear to be involved: attributes that are unique to humans and those that constitute essential "human nature." Denying uniquely human and human-nature attributes to other people may implicitly liken them to animals and automata, respectively. In the present study, the go/no-go association task was used to assess implicit associations among social categories exemplifying the two senses of humanness, traits representi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(81 citation statements)
references
References 18 publications
5
66
0
6
Order By: Relevance
“…In addition, the preliminary study found that human nature traits are associated with perceived mortality. Thus, denying one's human nature is indicative of perceiving the self as an object (Loughnan & Haslam, 2007;Loughnan et al, 2009) and as immortal. Studies 4 and 5 validated this interpretation by replicating the first three studies using measures assessing both the implicit and more explicit association of the self with objects.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, the preliminary study found that human nature traits are associated with perceived mortality. Thus, denying one's human nature is indicative of perceiving the self as an object (Loughnan & Haslam, 2007;Loughnan et al, 2009) and as immortal. Studies 4 and 5 validated this interpretation by replicating the first three studies using measures assessing both the implicit and more explicit association of the self with objects.…”
Section: Discussionmentioning
confidence: 98%
“…Even the seemingly benign, everyday experiences of women in which they use painful hot wax to remove hair from their bodies, undergo unnecessary cosmedc surgical procedures, or even have makeup permanently tattooed on their faces may be understood, in part, by these findings. To the extent that objectificadon is conceptualized as a denial of humanness in favor of an associadon with objects and other inanimate entities (Loughnan & Haslam, 2007), it stands to reason that women may be more willing and more able to engage in such behaviors because objects do not possess the ability to feel pain, feel hurt, or experience harm. Such theorizing could be tested by examining whether the manipulations in these studies also contribute a women's willingness to experience painful situadons.…”
Section: Implications Of Literal Objectification For Womenmentioning
confidence: 99%
“…One involves the perception of others as more machine-like, denying human nature attributes, and has been called mechanistic dehumanisation, while the other occurs when we have an animalised view of others, denying them uniquely human traits, and has been referred to as animalistic dehumanisation. This double view of dehumanisation is illustrated in a study by Loughnan and Haslam (2007). Using a go-no-go task the authors showed that artists, a social category pretested to be high in human nature, was indeed associated more with human nature traits, while business people were more easily associated with uniquely human traits.…”
Section: Differentiating Animalistic and Mechanistic Dehumanisationmentioning
confidence: 98%
“…Anthropomorphism has been operationalised in many di erent ways by di erent researchers [27,51]: from the humanness subscale of the revised Godspeed questionnaire [24], which quite straightforwardly asks the participant to rate the robots on scales like 'living versus inanimate' and 'humanmade versus humanlike' [41,67]; to home-cra ed questionnaires [15,49,50]; to mind a ribution questionnaires [12,14,64] and UH and HN a ribution measurements [37,52], which hold the (implicit) assumption of dehumanisation and anthropomorphism being each others opposite. is makes it virtually impossible to tease apart anthropomorphism, dehumanisation, and mind a ribution in the literature.…”
Section: Humanness and Aggressionmentioning
confidence: 99%